The effect of eye movement desensitization on neurocognitive functioning compared to retrieval-only in PTSD patients: a randomized controlled trial - Eka Susanty; Marit Sijbrandij; Wilis Srisayekti; Yusep Suparman; Anja C. Huizink (BMC Psychiatry)
Abstract Background There is robust evidence that posttraumatic stress disorder (PTSD) is associated with neurocognitive deficits, such as executive dysfunction or memory dysfunction. Eye Movement Desensitization and Reprocessing (EMDR) is an evidence-based treatment for PTSD, in which eye movements (EMs) are performed during traumatic memory retrieval. We examined whether Eye Movement Desensitization (EMD) improves neurocognitive functioning in PTSD patients, in comparison with a retrieval-only control condition without EMs. Methods Adult patients with PTSD (N = 91) were randomized into EMD (N = 47) or retrieval-only (N = 44). Data were collected at baseline (T0), one-week post-treatment (T1), one-month follow-up (T2), and at three-month follow-up (T3). Outcome measures were the California Verbal Learning Test (CVLT), the Trail Making Test (TMT), and the Digit Span Subtest of the Wechsler Adult Intelligence Scale fourth edition (WAIS-IV). We conducted linear mixed model to analyse the main outcomes. Results There was a main effect of time, indicating improvements for both the EMD and retrieval-only groups in CVLT scores, TMT A, TMT B and Digit Span score of WAIS-IV (Bonferroni-adjusted p’s < 0.001) from T0 to T3. There were no effects of group (p = .64) or group by time on CVLT total trial A (T3; p = .34), delay A (T3; p = .76), TMT A (T3; p = .61), TMT B (T3: p = .58), and Digit Span scores (T3; p = .78) of the WAIS-IV, indicating no significant differences between groups on any of the outcomes. Conclusion Comparing EMD and retrieval-only did not show evidence for additive effects of EMs on the treatment of PTSD in terms of improvements in neurocognitive functioning. Thus, treatments based on retrieval of traumatic memories may be used to improve neurocognitive functioning in patients with PTSD. Clinical trial registration The trial was registered 19/12/2017 at ClinicalTrials.gov, identifier [ISRCTN55239132].